OzoNews Volume XX - 28 February 2020 - United Nations Environment Programme (2020)
In this issue: 1. Kigali Amendment latest ratifications 2. Executive Committee Primer – 2020 3. The OzonAction new iPIC platform - The Informal Prior informed consent system (iPIC) has been completely overhauled and updated 4. The ozone layer and climate protection: Customs’ essential role 5. The unexpected link between the ozone hole and Arctic warming 6. Women working for the Montreal Protocol to protect the ozone 7. Enrollment in National Training and Support Programme for Refrigeration and AirConditioning (RAC) Servicing Sector technicians under the Montreal Protocol Programme of the Maldives 8. Qatar Ministry of Municipality and Environment Discusses Developments of Ozone Layer Protection 9. Protection of Stratospheric Ozone: Revisions to the Refrigerant Management Program’s Extension to Substitutes 10. GreenChill Webinar: Small and Independent Grocers Partnering with GreenChill 11. Delaware Department of Natural Resources and Environmental Control (DNREC) to launch refrigerant incentive program 12. Enforcing the EU F-Gas Regulation, what can Member States do? 13. Belarus stops importing ozone-depleting substances 14. Italy and Somalia meet on the Bosphorus: UNIDO-CSG Training on F-Gases and Alternatives to 12 Somali Technicians in Istanbul